Om Billedsproget i Grundtvigs sidste digt - Michelsen, William (Grundtvig-studier, 1994)
About the imagery in Grundtvig's last poem.Heritage and Prophecy. Grundtvig and the English-Speaking World. Edited by A.M. Allchin, D. Jasper; J.H. Schjørring and K. Stevenson. Aarhus University Press, Århus 1993. 330 s. ISBN 87 7288 447 9. Skrifter udgivet af Grundtvig-Selskabet, bind XXIV.Reviewed by William Michelsen